أهميّة مستشار العلاقات العامة في مجال التّدريب الإعلامي - محمودي, محمد بشير (جامعة الوادي - University of Eloued, 2019)
أضحى العمل في مؤسسات الإعلام والاتصال يقتضي ضرورة اختيار العاملين بها( الصحفيين والمراسلين..) اختيارًا دقيقًا نظرًا لـمسؤُولياتها الاجتماعية تُجاه الـمُجتمع التّي أصبحت مسؤُوليات ضخمة وخطيرة في آن واحد، هذه الـمسؤُوليات التّي أصبح لزامًا عليها إختيار أفضل للمُتقدّمين إليها ووضعهم في المكان الـمُناسب من خلال تكوينهم وتدريبهم في أداء العمل الإعلامي الذّي يتلائم مع مواهبهم وقُدراتهم ومُؤهلاتهم الذّي من شأنه أن يُؤدي إلى حُسن الأداء والإرتقاء بالـمهنة إلى مصاف الإحترافيّة وكسب قدرات اتصاليّة مُميزة تجعله مُميزًا عن باقي عاملي الـمـؤسسات الإعلامية الأخرى. هذا كُلّه وأكثر لا يتأتّى إلّا من خلال معرفة الأهميّة الوظيفيّة لخبير وأخصائي العلاقات العامة في مجال الإعلام من خلال خصائصه وصفاته ودوره في مجال العمل الإعلامي، ناهيك عن قدراته الاتصاليّة والمعرفيّة والعلميّة في سبيل رقي المُؤسّسة إلى مصاف عالية.The work in media and communication institutions necessitated the necessity to choose their employees (journalists and correspondents ..) a careful choice due to their social responsibilities towards society, which have become huge and dangerous responsibilities at the same time. And training them in performing media work that is compatible with their talents, abilities and qualifications, which would lead to good performance and upgrading the profession to the ranks of professionalism and gaining distinctive communication capabilities that make it distinguished from the rest of the workers of other media institutions. All this and more can only be achieved through knowing the functional importance of a public relations expert and specialist in the field of media through his characteristics, qualities and role in the field of media work, not to mention his communication, knowledge and scientific capabilities in order to elevate the institution to high ranks.
The importance of a public relations advisor in the field of media training
مقال
Keywords: المستشار، وظيفة العلاقات العامة، التّدريب، العمل الإعلامي; Counselor, public relations function, training, media work